An overview of an amplitude integrated EEG - Setyo Handryastuti (Indonesian Pediatric Society, 2007)
Amplitude integrated EEG (aEEG) has been used widely in developed countries for years. It was initially developed by Maynard and Prior 1 in the early 1970s and later adapted for neonatal use by Hellstrom-Westas and Svenningsen 2 . It is especially used for monitoring term newborns after having survived from birth asphyxia.During the last decade neonatal health care in Indonesia has developed. Monitoring of physiological parameters such as ECG, heart rate, blood pressure, oxygen saturation and temperature have been integrated inour neonatal intensive care unit but equipments like continuous EEG monitoring and aEEG to evaluate brain function have not been well-known among our neonatologists and pediatricians. The consequence is the de-crease of infant mortality was not associated with the improvement of quality of life of the survivors due to neurodevelopmental problems caused by various diseases during neonatal period. In the future, it can be prevented by using brain function monitoring in high risk newbornfor neurodevelopmental problem in conditions such as hypoxic-ischemic encephalopathy (HIE), prematurity, neonatal seizures, central nervous system infection, metabolic disorders, intraventricular or intracranial bleeding and brain malformation. This article gives an overview about aEEG and its role in newborn.Â